Wear-resistant metal ceramic powder and its application and wear-resistant metal ceramic

By designing specific chemical components, ratios and preparation processes, a wear-resistant cermet powder was prepared, which solved the problems of fluctuations in performance and insufficient wear resistance during the preparation process of M3B2 cermet, and achieved comprehensive performance of high hardness, wear resistance, corrosion resistance and high temperature oxidation resistance.

CN114309578BActive Publication Date: 2025-03-14WUHAN JUNENG TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110303402.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-03-14
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

During the preparation process, M3B2 metal cermets have problems such as high oxygen content and difficult to control density, resulting in large performance fluctuations. At the same time, its wear resistance and hardness are difficult to meet the requirements in some applications.

Method used

By designing specific chemical components and ratios, a wear-resistant cermet powder is prepared, which includes specific contents of Mo, B, Cr, Ni, V, Nb, W, Co, Mn, Ti and Fe, and metal cermet is prepared through aerosol powdering process and thermal isostatic pressing process.

Benefits of technology

The uniform distribution of metal cermets and no macroscopic alloy elements segregation is achieved. The second phase is mainly a metal cermet phase, and the structure is composed of a large number of fine granular hard metal cermet phases and iron matrix, and has excellent wear resistance, high temperature oxidation resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114309578B_ABST
    Figure CN114309578B_ABST
Patent Text Reader

Abstract

The present invention provides a wear-resistant metal ceramic powder and its application and wear-resistant metal ceramic, wherein the chemical components of the wear-resistant metal ceramic powder include, by mass percentage: (C+N): 0.1%-1.6%, Mn: 0.1%-3.0%, Cr: 4%-20%, W: ≤12%, Mo: 20%-55%, V: ≤4%, Nb: ≤4%, Co: ≤3%, Ti: 0.2%-6%, Ni: 3%-10%, B: 2%-8%, and the remainder is Fe and impurities. The wear-resistant metal ceramic powder of the present invention is composed of a large number of fine granular hard metal ceramic phases and an iron matrix in its structure, and a large number of high-hardness, high-melting-point metal ceramic phases exist. The product prepared by using the wear-resistant metal ceramic powder has excellent wear resistance and high temperature resistance, and also has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal ceramic materials, and in particular to a wear-resistant metal ceramic powder. At the same time, the present invention also relates to the application of the wear-resistant metal ceramic powder and a wear-resistant metal ceramic prepared from the wear-resistant metal ceramic powder. Background Art

[0002] Metal ceramics have both metallic and ceramic properties. For example, a typical M3B2 metal ceramic, with Fe as the matrix and ternary boride as the hard second phase, has high wear resistance, hardness, and high temperature oxidation resistance. Based on this characteristic, this type of metal ceramic has been successfully applied in some specific fields, including high temperature and wear resistant parts, non-ferrous metal processing tool molds, injection molding screws, and parts surface coatings.

[0003] However, as the requirements for material performance in the application fields continue to increase, some shortcomings of metal ceramics in terms of quality and performance have become prominent. Mainly manifested in the following aspects:

[0004] 1. M3B2 metal ceramics are mainly prepared by traditional liquid phase sintering process, which has a long process flow and is difficult to avoid such problems as high oxygen content in the product and difficulty in controlling density, resulting in large performance fluctuations.

[0005] 2. The key properties of M3B2 metal ceramics, such as wear resistance and hardness, rely on the high content of ternary borides formed by reactions in the matrix, which will reduce the bending strength to a certain extent, and the load-bearing parts are prone to breakage when subjected to large loads. Summary of the invention

[0006] In view of this, the present invention aims to provide a wear-resistant metal ceramic powder so that the product prepared therefrom has excellent wear resistance.

[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0008] A wear-resistant metal ceramic powder, whose chemical components, measured by mass percentage, include: (C+N): 0.1%-1.6%, Mn: 0.1%-3.0%, Cr: 4%-20%, W: ≤12%, Mo: 20%-55%, V: ≤4%, Nb: ≤4%, Co: ≤3%, Ti: 0.2%-6%, Ni: 3%-10%, B: 2%-8%, and the balance is Fe and impurities.

[0009] Furthermore, its chemical composition, by mass percentage, includes: (C+N): 0.1%-0.8%, Mn: 0.1%-3.0%, Cr: 4%-20%, W: ≤12%, Mo: 20%-55%, V: 0.2%-4%, Nb: ≤4%, Co: ≤3%, Ti: 0.2%-3%, Ni: 3%-10%, B: 2%-8%.

[0010] Furthermore, the impurities include O, and O: ≤0.03%.

[0011] Furthermore, the impurities include S, and S: ≤0.3%.

[0012] Furthermore, the impurities include P, and P: ≤0.05%.

[0013] Furthermore, the volume fraction of the metal ceramic phase in the wear-resistant metal ceramic is 20%-60%.

[0014] Furthermore, the particle size of the metal ceramic phase is ≤8 μm, and at least 80% of the particle size of the metal ceramic phase is ≤5 μm.

[0015] Here, the design concept of the present invention is briefly described. In the present invention, specific chemical composition and ratio are necessary conditions for achieving its comprehensive performance. The functions and principles of each chemical component are briefly described as follows:

[0016] Mo and B react with the matrix Fe to form an M3B2 type ceramic phase, which can improve wear resistance. In the present invention, the suitable content range of Mo is 20%-55%, the suitable content range of B is 2%-8%, and the suitable range of Mo / B molar ratio is: 0.8-1.2.

[0017] Cr is solid-dissolved in the matrix and the precipitated phase at the same time, which can improve the corrosion resistance and the morphology of the second phase. In the present invention, the appropriate content range of Cr is 4%-20%.

[0018] Ni is solid-dissolved in the matrix, which can improve the corrosion resistance. In the present invention, the suitable content range of Ni is 3%-10%.

[0019] V and Nb are mainly used to improve the precipitation morphology of M3B2 and enhance toughness. In the present invention, the suitable content range of V is ≤4%, preferably 0.2%-4%, and the suitable content range of Nb is ≤4%.

[0020] W is an optional element, which is also used to improve the precipitation morphology of M3B2 and improve toughness. In the present invention, the appropriate content range of W is ≤12%.

[0021] Co is an optional element used to improve the hardness of the matrix. In the present invention, the appropriate content range of Co is ≤3%.

[0022] Mn is dissolved in the matrix to improve the toughness of the matrix. In the present invention, the appropriate content range of Mn is 0.1%-3.0%.

[0023] Ti reacts with C and N to form an MX type metal ceramic phase, where M represents an element mainly composed of Ti and X represents an element mainly composed of C or N, to improve wear resistance. In the present invention, the appropriate content range of Ti is 0.2%-6%, preferably 0.2%-3%. C and N elements are interchangeable, and the appropriate content range of (C+N) is 0.1%-1.6%, preferably 0.1%-0.8%.

[0024] Fe is the matrix, and it cooperates with Mo and B to form an M3B2 type ceramic phase to improve the wear resistance.

[0025] In addition to the chemical components set above, the wear-resistant metal ceramic powder of the present invention has a Fe matrix as the balance, and of course also includes some inevitable residual trace elements, including O, S, P, etc. In order to prevent adverse effects on the mechanical properties of the alloy, the appropriate content range of O is required to be ≤0.03%, the appropriate content range of S is ≤0.3%, and the appropriate content range of P is ≤0.05%.

[0026] In addition, in the chemical composition of the present invention, impurities may also include at least one of Zr, Mg, Al, Cu, Sn and Pb, and the total amount of these impurities is not more than 1%.

[0027] The wear-resistant metal ceramic of the present invention is prepared by selecting appropriate chemical components and proportions, the volume fraction of the metal ceramic phase in the alloy is 20-60%, the types include M3B2 type and MX type, and the particle size of the metal ceramic phase in the alloy is ≤8μm, and at least 80% of the metal ceramic phase particles have a size of ≤5μm.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] The key to the wear-resistant metal ceramic powder described in the present invention is to select appropriate chemical components and proportions so that it has a uniformly distributed second phase structure without macroscopic alloy element segregation. The second phase is mainly a metal ceramic phase, and the structure is composed of a large number of fine granular hard metal ceramic phases and an iron matrix. The presence of a large number of high-hardness, high-melting-point metal ceramic phases, therefore, the product prepared using the wear-resistant metal ceramic powder has excellent wear resistance and high-temperature oxidation resistance, as well as excellent corrosion resistance.

[0030] In addition, the wear-resistant metal ceramic of the present invention has a hardness of 58HRC-70HRC and a bending strength of more than 2000MPa, and is suitable for manufacturing various wear-resistant, corrosion-resistant and high-temperature-resistant parts.

[0031] At the same time, the present invention also relates to a method for preparing the wear-resistant metal ceramic powder. The wear-resistant metal ceramic powder is prepared by adopting a gas atomization powder making process.

[0032] In addition, the present invention also relates to a wear-resistant metal ceramic, which is prepared by using the wear-resistant metal ceramic powder and a hot isostatic pressing process.

[0033] In addition, the present invention also relates to the application of the wear-resistant metal ceramic powder, which is formed on the surface of a substrate by laser cladding, spraying or surfacing process.

[0034] The wear-resistant metal ceramic powder of the present invention is molded on the surface of a substrate, or the wear-resistant metal ceramic of the present invention is prepared, which has the same beneficial effects as the wear-resistant metal ceramic powder relative to the prior art, and will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0036] Figure 1 This is a microstructure picture of the comparative example Cr12MoV of the present invention;

[0037] Figure 2 This is a microstructure picture of the wear-resistant metal ceramic described in Example 2 of the present invention;

[0038] Figure 3 This is a microstructure picture of the wear-resistant metal ceramic described in Example 3 of the present invention;

[0039] Figure 4 It is a schematic diagram comparing the relative wear resistance of various embodiments of the wear-resistant metal ceramics described in the present invention. DETAILED DESCRIPTION

[0040] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0041] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0042] In order to improve the comprehensive performance of M3B2 metal ceramics, the present invention has made breakthroughs and innovations in two aspects: alloy design concept and preparation process. First, the present invention first relates to a wear-resistant metal ceramic powder, which defines a specific chemical composition and ratio, and according to the design characteristics of the chemical composition of the present invention, it is preferably prepared by a rapid solidification process to avoid alloy element segregation.

[0043] Specifically, the rapid solidification process preferably adopts a powder metallurgy process. The wear-resistant metal ceramic powder of the present invention is first prepared by a gas atomization powder making process, and then the wear-resistant metal ceramic is prepared by a hot isostatic pressing process. In addition, the aforementioned wear-resistant metal ceramic powder can also be used in combination with laser cladding, spraying or surfacing technology to perform local alloying processing on the surface of the substrate.

[0044] It should be noted that the gas atomization powder making process described in the present invention includes the following process: using an inert gas, such as nitrogen or argon, to atomize and spray-cool the molten alloy liquid having the alloy components of the present invention, so that the alloy melt is instantly solidified into fine, nearly spherical powder particles.

[0045] In addition, the hot isostatic pressing process described in the present invention includes the following process: placing the alloy powder prepared by the gas atomization powder making process in a metal sheath, evacuating it and exhausting the gas in the sheath and then welding and sealing it, placing the powder-filled and sealed sheath in a hot isostatic pressing furnace, and achieving complete densification of the powder in the sheath under conditions of a temperature exceeding 1000°C and a pressure exceeding 100MPa, thereby forming an ingot.

[0046] The present invention will now be described in conjunction with several specific embodiments, which can be specifically referred to as shown in Table 1.

[0047] Table 1: Chemical composition of various examples of alloys

[0048]

[0049] Examples 1 to 9 are the chemical components of the wear-resistant metal ceramic powder of the present invention, which are prepared by powder metallurgy. The powder is first prepared by gas atomization powder making process, and then the powder is densified by hot isostatic pressing, and then made into rods with a diameter of 50 mm.

[0050] The atomization powder making process steps and process parameters are as follows:

[0051] a. The alloy of the present invention is loaded into a smelting ladle and powered for heating under a protective atmosphere;

[0052] b. After the alloy is melted, continue to heat it to 1800°C, take samples and analyze the composition, and then adjust it to the qualified range;

[0053] c. Preheat the atomizing tundish crucible, and the tundish temperature reaches 1000℃ before the alloy melt is atomized;

[0054] d. After the alloy melt temperature reaches the required level, turn on the high-pressure atomizing gas and exhaust fan.

[0055] The ceramic leak at the bottom of the interlayer package enters the atomization system, starting the atomization of the alloy melt, and the atomization flow rate of the alloy melt is controlled at 20kg / min;

[0056] e. The atomized powder is transported to the powder collecting tank by air flow and cooled to 50℃.

[0057] The hot isostatic pressing process is as follows:

[0058] a. Place the alloy powder prepared by gas atomization powder making process in a metal sheath and evacuate it.

[0059] Exhaust the gas in the package and then weld and seal it;

[0060] b. Place the powder-filled and sealed package in a hot isostatic pressing furnace at a temperature of 1100°C and a pressure of 110 MPa.

[0061] Under the conditions, the powder in the package is completely densified to become a hot isostatic pressed ingot.

[0062] It should be noted that in Example 9, due to the premature precipitation of the ceramic phase during the cooling process of the molten metal, the molten metal is prone to atomization and leak blockage, making stable production difficult.

[0063] Next, the wear-resistant metal ceramics of Examples 1 to 9 in Table 1 were compared and tested in the following aspects: (1) microstructure after heat treatment; (2) hardness; (3) wear resistance; (4) corrosion resistance. The comparison results are as follows:

[0064] (1) Microstructure after heat treatment

[0065] The microstructures of the wear-resistant metal ceramics of Examples 1 to 8 are analyzed. For the sake of comparison, the microstructure morphology of a purchased general standard tool steel Cr12MoV is also given. Figure 1 The microstructures of Example 2 and Example 3 are shown in Figure 2 and Figure 3 As shown. The results show that the wear-resistant metal ceramics of Examples 1 to 7, the metal ceramic second phase particles prepared by powder metallurgy process are fine and uniformly distributed, without macroscopic alloy element segregation and pores. Based on composition and morphology analysis, the metal ceramic phase includes M3B2 type and MX type, with a volume fraction of 20-60%, the metal ceramic phase particle size is ≤8 microns, and at least 80% of the metal ceramic phase particle size is ≤5 microns. The high-hardness ceramic particle phase is distributed in the matrix in a fine and dispersed manner, which can improve the wear resistance without excessively damaging the machinability.

[0066] (2) Hardness

[0067] The hardness of the wear-resistant metal ceramics of Examples 1 to 8 was tested, and the results are shown in the table below.

[0068] Table 2: Hardness test was performed on each embodiment, and the results are as follows:

[0069]

[0070] Referring to GB / T 230.1-2018, the hardness of Examples 1 to 8 was measured respectively using a Rockwell hardness tester. The results showed that the wear-resistant metal ceramics of the present invention can achieve a high hardness level.

[0071] (3) Wear resistance

[0072] The wear resistance of the alloy was tested by metal-to-metal friction test, with the friction pair being 45# steel, the load being 50kg, and the speed being 200r / min. The wear resistance was measured based on the weight loss of the tested material and was divided into 10 levels of wear resistance, with 1 being the worst wear resistance and 10 being the best wear resistance.

[0073] At the same time, a standard tool steel grade Cr12MoV is selected as a comparison of wear resistance, and the heat treatment process parameters of the Cr12MoV alloy are quenching at 1020°C and tempering at 520°C twice, each time for 2 hours. The comparison results are shown in Figure 4. The wear-resistant metal ceramics of the present invention all show excellent wear resistance. At the same time, it can be seen from the comparison between Example 2 and Example 3 that the MX type metal ceramic formed by Ti has a significant effect on improving the wear resistance.

[0074] In Example 8, due to the small amount of Ti added, the improvement on the wear resistance is relatively unobvious.

[0075] (4) Corrosion resistance

[0076] Examples 1 to 8 and the comparative example were corroded by immersion in 5% nitric acid ethanol solution. After immersion for 1 hour, the surface corrosion state was observed, 0 represents no corrosion point, and 10 represents that the entire surface is corroded.

[0077] Table 3 Corrosion resistance comparison

[0078]

[0079] The results are shown in Table 3. The surfaces of the alloys of Examples 1 to 8 all remained free of corrosion spots, showing good corrosion resistance.

[0080] In the description of this specification, embodiments of the present invention are given. It can be understood that the above embodiments are exemplary and cannot be understood as limitations on the invention. Without contradiction, ordinary technicians in this field can combine, combine, replace and deform the features of different embodiments or examples described in this specification.

Claims

1. A wear-resistant metal ceramic powder, characterized in that: Its chemical composition by mass percentage includes: (C+N): 0.1%-0.8%, Mn: 0.1%-3.0%, Cr: 4%-20%, W: ≤12%, Mo: 20%-55%, V: 0.2%-4%, Nb: ≤4%, Co: ≤3%, Ti: 0.2%-3%, Ni: 3%-10%, B: 2%-8%, and the balance is Fe and impurities; The volume fraction of the metal ceramic phase in the wear-resistant metal ceramic powder is 20%-60%, the particle size of the metal ceramic phase is ≤8 μm, and at least 80% of the particle size of the metal ceramic phase is ≤5 μm.

2. The wear-resistant metal ceramic powder according to claim 1, characterized in that: The impurities include O, and O: ≤0.03%.

3. The wear-resistant metal ceramic powder according to claim 1, characterized in that: The impurities include S, and S: ≤0.3%.

4. The wear-resistant metal ceramic powder according to claim 1, characterized in that: The impurities include P, and P: ≤0.05%.

5. The method for preparing the wear-resistant metal ceramic powder according to any one of claims 1 to 4, characterized in that: The wear-resistant metal ceramic powder is prepared by adopting a gas atomization powder making process.

6. A wear-resistant metal ceramic, characterized in that: The wear-resistant metal ceramic is made of the wear-resistant metal ceramic powder according to any one of claims 1 to 4 and is prepared by a hot isostatic pressing process.

7. The use of the wear-resistant metal ceramic powder according to any one of claims 1 to 4, characterized in that: The wear-resistant metal ceramic powder is formed on the surface of the substrate by laser cladding, spraying or surfacing.

Citation Information

Patent Citations

  • Preparation method of powder metallurgy tool and mould steel

    CN102909385A

  • Metal ceramics and preparation method thereof

    CN105177390A

  • Metal base ceramic phase reinforced alloy tool steel powder for 3D printing, preparation method and application thereof

    CN105714209A

  • Heat-resistant wear-resistant metal ceramic flux-cored wire for surfacing

    CN109623195A

  • Metal ceramic and its preparation method

    CN1410575A